Weakly Nonlocal Hamiltonian Structures: Lie Derivative and Compatibility - Sergyeyev, A. (Symmetry, Integrability and Geometry: Methods and Applications, 2007)
We show that under certain technical assumptions any weakly nonlocal Hamiltonian structure compatible with a given nondegenerate weakly nonlocal symplectic structure J can be written as the Lie derivative of J −1 along a suitably chosen nonlocal vector field. Moreover, we present a new description for local Hamiltonian structures of arbitrary order compatible with a given nondegenerate local Hamiltonian structure of zero or first order, including Hamiltonian operators of the Dubrovin-Novikov type.